Solving the Capacitated Vehicle Routing Problem with Heterogeneous Fleet Using Heuristic Algorithm in Poultry Distribution - Yulinda Uswatun Kasanah; Nabila Noor Qisthani; Aswan Munang (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
The problem that is often experienced in the delivery of goods from distributor to the destination is the delivery route that is not sufficient with the vehicle's capacity. This matter is crucial because it can affect the clients' trust on the shippers in the distributor. This problem can be analyzed using Capacitated Vehicle Routing Problem (CVRP) with Clarke and Wright Algorithm. This research begins with determining the distance between all coordinates with Euclidean Distance, making the distance matrix between places to go. After that, the calculation CVRP using Clarke and Wright Algorithm is exected in this study, a calculate CVRP using Clarke and Wright algorithm can help of Python. The study was conducted at 16 customers coordinates, the results obtained by 4 routes with total load 4751 kg and distance 436 km. Route of delivery the first route 924 kg load and distance 80 km, second route 962 kg load and distance 112 km, third route 1450 kg load and distance 144 km, and the fourth route 1415 kg load and distance 100 km.